MULTIDISCIPLINARY TEAM IN TREATMENT OF HIGH ENERGY TRAUMA OF LEFT LOWER LEG– CASE REPORT - Gadzevska Tomulevska, Ilina; Mitev, Konstantin; Taushanov, Mihail (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
High- energy fractures of lower leg are complex lesions that may be associated with soft tissue damage and severe complications, such as compartment syndrome and infection. This case report interests a professional motocross freestyler with complex tibia and fibular open fracture, with soft tissue damage.  Case presentation  We report the case of 31-year-old man, presented with injuries resulting from accident, as professional freestyler motorcyclist, including open horizontal multifragmentary fracture with angulation of the proximal and middle part of the left tibia and horizontal fracture with angulation of the proximal and middle part of the left fibula. The initial assessment revealed surgical stabilization of the tibia, intramedullary osteosynthesis with wedge. The open lacero-contused wound of the anterior lower leg after the surgery complicated with infection. Necrectomy and Suprasorb A + Ag dressing was performed for per secondar healing of the wound.  Conclusion  For mounts later, despite the complexity of the fractures, the gravity of the soft tissue lesion and subsequent complications, the patient healed. This satisfactory result depended on the correct management in terms of type of treatment and timing. It highlights the importance of a multidisciplinary approach, incorporating trauma surgeons, plastic and reconstructive surgeon and intensive care specialist to navigate the intricacies of high energy trauma care.  Keywords: injuries, soft tissue damaged, osteosynthesis.